Preparation and Optimization of Protein–DNA Complexes Suitable for Detailed NMR Studies - Sam, My D. (2012)
This chapter describes the methods to form and optimize samples of protein–DNA complexes that are suitable for detailed structure and dynamics studies by NMR spectroscopy.